SOYBEAN DEVELOPMENT AND PRODUCTIVITY AS A FUNCTION OF NPK FERTILIZATION AND INOCULATION WITH CONDITIONING BACTERIA - Aritana Wilton Ferreira, Cicero; Biotech Brasil, Green; Theo Gentil, Kevin (Journal of Interdisciplinary Debates, 2021)
Soybean (Glycine max L.) is a legume originated in Asia, was domesticated about 4500-4800 years ago. The first report of soybean cultivation in Brazil was in 1882 in the state of Bahia. In recent years soybean cultivation has reached a high productivity index, due to the investment in balanced fertilization and genetic improvement, which together are able to raise the productive potential in the plant, together with other management practices. The nutrients required in larger amounts are nitrogen (N), potassium (K) and phosphorus (P). Therefore, the present study had as objective to evaluate the development and productivity of the soybean as a function of the inoculation of bacteria in the seeds and chemical fertilization with NPK at sowing. The experiment was conducted in the experimental area of the Centro de Ciências Agrarias e da Biodiversidade (CCAB), of the Universidade Federal do Cariri (UFCA), in Crato - CE. The experiment was carried out in a randomized block design, in a 4x2 subdivided plot, with four replications, totaling 32 experimental plots. The plots were four doses of NPK (0, 25, 50 and 100% of the recommended dose) and the subplots referring to the use of conditioning bacteria from Barvar company (WITH and WITHOUT). The data were submitted to analysis of variance by the F test and the Barvar factor averages compared by the Tukey test at 5% probability and the NPK dose factor was submitted to regression analysis. The statistical program Sisvar 5.3 was used for the statistical analysis. The variables analyzed were plant height, height of insertion of the first pod, number of branches, number of pods, mass of pods, mass of 100 grains, grain mass and yield. For the fertilization factor the variables are plant height, pod mass, grain mass and yield showed significant results at 1 and 5%, respectively. The increase in the doses of NPK applied provided improvements for plant height, pod mass, grain mass and productivity. The use of inoculation with Barvar provided an increase in the development and productivity of soybean, with an increase of 11% in soybean yield. The interaction between Barvar inoculation and NPK doses did not influence the development and productivity of soybean.